Defining and Clarifying the Terms Canine Possessive Aggression and Resource Guarding: A Study of Expert Opinion - Jacobs, Jacquelyn A.; Coe, Jason B.; Widowski, Tina M.; Pearl, David L.; Niel, Lee (Frontiers in Veterinary Science, 2018)
The terms possessive aggression and resource guarding are often used interchangeably to describe behavior patterns used by a dog to control primary access to a perceived valuable item. The use of inconsistent terminology may impact the effectiveness of communication between dog owners and clinicians, affect treatment and management success for the behavior, and inhibit research progress. The aim of this study was to explore the opinions of canine behavior experts on the meaning of and preference for the terms possessive aggression and resource guarding, as well as to develop and propose an operational ethological definition for the preferential term identified. Eighty-five individuals met the inclusion criteria and were invited to participate in a two-stage online survey. Results from the two-stage survey found that the majority of participants preferred the term resource guarding. Detailed exploration of meaning and definitions required in-depth discussion beyond traditional survey methods, therefore, respondents from the second stage of the survey were invited to participate in an online discussion board. Considering 100% consensus was not reached regarding terminology among experts in the field, future authors and clinicians should provide clear definitions where terms are applied to ensure effective communication between all parties and to ensure consistency in canine behavior research. Based on expert contributions, we define resource guarding as "the use of avoidance, threatening, or aggressive behaviors by a dog to retain control of food or non-food items in the presence of a person or other animal".